Emerging Biosensing Technologies for Neuroinflammatory and Neurodegenerative Disease Diagnostics - Abreu, Catarina M.; Soares-dos-Reis, Ricardo; Melo, Pedro N.; Relvas, João B.; Guimarães, Joana; Sá, Maria José; Cruz, Andrea P.; Mendes Pinto, Inês (Frontiers in Molecular Neuroscience, 2018)
Neuroinflammation plays a critical role in the onset and progression of many neurological disorders, including Multiple Sclerosis, Alzheimer’s and Parkinson’s diseases. In these clinical conditions the underlying neuroinflammatory processes are significantly heterogeneous. Nevertheless, a common link is the chronic activation of innate immune responses and imbalanced secretion of pro and anti inflammatory mediators. In light of this, the discovery of robust biomarkers is crucial for screening, early diagnosis and monitoring of neurological diseases. However, the difficulty to investigate biochemical processes directly in the central nervous system is challenging. In recent years, biomarkers of central nervous system inflammatory responses have been identified in different body fluids, such as blood, cerebrospinal fluid and tears. In addition, progress in micro and nanotechnology has enabled the development of biosensing platforms capable of detecting in real-time, multiple biomarkers in clinically relevant samples. Biosensing technologies are approaching maturity where they will become deployed in community settings, at which point screening programs and personalized medicine will become a reality. In this multidisciplinary review, our goal is to highlight both clinical and recent technological advances towards the development of multiplex based solutions for effective neuroinflammatory and neurodegenerative disease diagnostics and monitoring.